HydroCloud: A Web Application for Exploring Stream Gage Data - Martin C. Roberge; Michael P. McGuire; Jie Lian (Journal of Open Research Software, 2017)
HydroCloud (hydrocloud.org) is a mobile-friendly web application for visually browsing hydrology data from multiple sources. Data providers such as the US Geological Survey (USGS) and the German 'Wasserstraßen- und Schifffahrtsverwaltung des Bundes' (WSV) currently serve stream discharge data from more than 10,000 stream gages around the world. HydroCloud allows users to plot these data while out in the field, while also providing contextual information such as the current NEXRAD weather imagery or descriptive information about the stream gage and its watershed. Additional features include a chat mechanism for contacting developers, and the use of local storage for saving data.   Funding Statement: This project was supported in part by a grant from the Towson University School of Emerging Technology.